2017
DOI: 10.1590/0074-02760160523
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria decision analysis and spatial statistic: an approach to determining human vulnerability to vector transmission of Trypanosoma cruzi

Abstract: BACKGROUND Chagas disease (CD), caused by the protozoan Trypanosoma cruzi, is a neglected human disease. It is endemic to the Americas and is estimated to have an economic impact, including lost productivity and disability, of 7 billion dollars per year on average.OBJECTIVES To assess vulnerability to vector-borne transmission of T. cruzi in domiciliary environments within an area undergoing domiciliary vector interruption of T. cruzi in Colombia.METHODS Multi-criteria decision analysis [preference ranking met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…The likelihood of human contact is influenced by short-distance movement (for example, whether the species enters and/or colonises homes) and the larger-scale geographical distribution of that species. Studies assessing vulnerability of individuals to Chagas disease have shown that, while housing, ecotype and socio-economics are all relevant, triatomine presence is the most important indicator [4]. Thus understanding the distribution of these vector species is vital to both target control measures and to assess disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…The likelihood of human contact is influenced by short-distance movement (for example, whether the species enters and/or colonises homes) and the larger-scale geographical distribution of that species. Studies assessing vulnerability of individuals to Chagas disease have shown that, while housing, ecotype and socio-economics are all relevant, triatomine presence is the most important indicator [4]. Thus understanding the distribution of these vector species is vital to both target control measures and to assess disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…La información aportada por los usuarios de la app puede ser analizada por técnicas de aprendizaje automático (machine learning), análisis de árboles de decisión o redes neurales artificiales, entre otras técnicas de inteligencia artificial (30). Las técnicas de inteligencia artificial, combinadas con técnicas cartográficas, son herramientas útiles para buscar, predecir, vigilar y controlar focos de infecciones humanas (22,(31)(32)(33). Se propone emplear estas técnicas porque permiten manejar mejor la cantidad de variables y el análisis de datos masivos en comparación con un agente humano.…”
Section: Propuesta De Modelo De Atención En El Lugarunclassified
“…Multi-criteria decision analysis is a method that approaches a certain object from different characteristics that influence the occurrence of a given problem. The method has become increasingly used for understanding of events of interest in public health [54].…”
Section: Analysis Of Datamentioning
confidence: 99%